EFFECTS OF NACI STRESS ON THE GENOME STRUCTURE STABILISATION OF RICE ORYZA SATIVA CELLS LONG-TERM CULTURED IN VITRO - Thuỷ, Nguyễn Thanh; Bình, Đỗ Quang (Vietnam Journal of Biotechnology, 2011)
In vitro culture of plant cells is a useful tool for studies relating the biological fransformation from a single cell to the whole plant in vitro. Using the in vitro technology, researchers are able to not only confrol the biological reaction chains but also to create a number of new products other than those ofthe initial materials. However, growing in the in vitro artificial conditions for a long time, plant cells could not avoid the phenomenon of soma variation. The level of variation of the cultured cells depends on various factors, including the genotype and physiological state of initial materials, the culture conditions, the culture time, etc. This study presents results relating the molecular changes in the genome of rice (Oryza sativa) cells that have been cultured for a long time in different salt (NaCI) sfress conditions by RAPD technique. In comparison with the initial material, not derived from the culture in vitro of isolated cells, genome of cells cultured in a condition without NaCI sfress bears more molecular changes than that of cells continuously cultured in the salt sfress condition. Though cells of the two culture conditions shared several specific changes, induced by the long-term culture in vitro, the salt sfress adapted cells shared more common similarities with the initial material than the non sfressed cells. Results obtained from the present study are in accordance with our previous observations, carried out at the cell level, that the totipotency ofthe isolated rice cells has been stabilized much better in the suitable salt sfress culture condition than in the condition without the sfress factor.